2002
DOI: 10.1148/radiographics.22.2.g02mr01351
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial Carcinoid Tumors of the Thorax: Spectrum of Radiologic Findings

Abstract: Bronchial carcinoid tumors are neuroendocrine neoplasms that range from low-grade typical carcinoids to more aggressive atypical carcinoids and therefore demonstrate a wide spectrum of clinical behaviors and histologic features. Typical and atypical bronchial carcinoids have similar imaging features. Because most bronchial carcinoids are located in central airways, radiologic findings are usually related to bronchial obstruction. Central bronchial carcinoids manifest as an endobronchial nodule or hilar or peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
141
0
9

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 201 publications
(154 citation statements)
references
References 45 publications
4
141
0
9
Order By: Relevance
“…Well-defined, centrally located tumors involving the airway with calcification, punctate or diffuse, are considered characteristic on CT scan. 21 However, additional investigation and staging with fluorodeoxyglucose (FDG) -PET scanning remains controversial. Due to the lower metabolic activity of carcinoid tumors, FDG uptake in PET scanning often demonstrates low uptake (equivocal in comparison to mediastinal uptake) compared with high-grade nonsmall cell cancers.…”
Section: Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Well-defined, centrally located tumors involving the airway with calcification, punctate or diffuse, are considered characteristic on CT scan. 21 However, additional investigation and staging with fluorodeoxyglucose (FDG) -PET scanning remains controversial. Due to the lower metabolic activity of carcinoid tumors, FDG uptake in PET scanning often demonstrates low uptake (equivocal in comparison to mediastinal uptake) compared with high-grade nonsmall cell cancers.…”
Section: Presentationmentioning
confidence: 99%
“…It has also been reported that tumors are more common in the right lung, presumably related to the larger at-risk area of lung. 13,18,21 …”
Section: Stagingmentioning
confidence: 99%
“…It accounts for 0.5-2.5% of all primary lung tumours, and is subdivided into typical (80%) and atypical (20%) types [1] . It has a mean age of presentation of 45 years, younger than that for conventional bronchogenic carcinoma [33] . Typical carcinoid usually appears as a solitary, well-defined 1-3 cm oval or lobulated soft tissue nodule [1] .…”
Section: Airwaysmentioning
confidence: 99%
“…In 15% of cases it arises within the lung periphery, in which case it may not be directly related to an airway on gross inspection [1] . Rarely, tumours are irregular or ill-defined [1,33] . Most endobronchial carcinoids have a large extraluminal component, and for this reason are termed 'iceberg' lesions [34] .…”
Section: Airwaysmentioning
confidence: 99%
See 1 more Smart Citation